Commercial antagonists for the management of fungal diseases of strawberry crops (Fragaria x ananassa Duch.), in the municipality of Pamplona, Norte de Santander (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2024)
Fungal diseases in strawberry crops are a major problem for farmers in the municipality of Pamplona Norte de Santander, which is why it is important to look for possible solutions that help mitigate the incidence and severity of these diseases. The general objective of this work was to evaluate commercial antagonists for the management of fungal diseases in strawberries. A field experiment was carried out with complete random blocks of eight treatments with four repetitions of which three were chemical fungicides, the mixture of chemical fungicides, two biological treatments, the mixture of biologicals and the farmer's management. In the statistical analyzes no significant statistical differences were obtained, but it was observed that the products had a positive effect on the control of these diseases and the biological products stand out mainly since these not only control crop diseases, but can also stimulate the plant for its good development unlike chemical products that are specific to control diseases, in the same way biological products are a good alternative because they are shown to be equal and in some cases better than chemical treatments.
Keywords: Bioproducts; diseases; biological control; incidence; severity